Factors that affect the accuracy of submitting SKPK Treasurer Accountability Reports to the Aceh Tamiang Regency Government: Faktor-Faktor yang Mempengaruhi Ketepatan Penyampaian Laporan Pertanggungjawaban Bendahara SKPK pada Pemerintah Kabupaten Aceh Tamiang - Nurmala, Eka; Sultan, Sultan; T. M. Jamil; Arfah, Mahbub; Wibisono, Yohan (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2024)
The application of accounting standards in the country in the management of regional finance has an impact on regional budget implementation responsibility reports (APBD). This type of research is quantitative descriptive and describes the relationship between independent and dependent variables. Meanwhile, human resource factors, treasurer facilities, and infrastructure, treasurer's term of office, regulations, the intensity of management training, and accountability of SKPD treasurers, as well as unclear roles in the Aceh Tamiang district government have a big influence—the impact of the timeliness of submitting regional government accountability reports. In several cases, the variable intensity of administrative training and responsibilities of SKPD accountants (X5), as well as the ambiguity of the role (X6) produced a positive impact on the timeliness of government reporting in the regions.